Pengukuran Nilai Target Strength Ikan Lele (Clarias batrachus) Menggunakan Metode Hidroakustik SIMRAD EK15 Kondisi Terkontrol - Santoso, Hendi; Pujiyati, Sri; Hestirianoto, Totok; Jaya, Indra; Priatna, Asep (Jurnal Perikanan Unram, 2025)
Catfish (Clarias batrachus) is one of the main commodities in Indonesia's freshwater aquaculture industry. Accurate monitoring of fish growth and population is crucial to improving production efficiency and sustainability. Conventional methods such as physical weighing are often inefficient and may cause stress to the fish. Therefore, hydroacoustic technology offers a promising alternative due to its non-invasive nature and ability to provide real-time data. This study aims to estimate the Target Strength (TS) of catfish using hydroacoustic methods with a SIMRAD EK15 instrument under controlled environmental conditions. The measurements were conducted in a test tank where physical parameters such as temperature, salinity, and water clarity were maintained consistently to ensure reliable results. The experiment involved 13 catfish of various sizes, with body lengths ranging from 8.1 cm to 19.3 cm and weights from 4 to 37 grams. The measured TS values ranged from -64.81 dB to -59.89 dB. The results indicated a positive correlation between TS and both fish length and weight, suggesting that larger fish produced stronger acoustic backscatter signals. This study provides a valuable foundation for the application of hydroacoustic methods in catfish population surveys, both in controlled environments and natural waters. The findings can be adapted to support more efficient and sustainable fish farming practices through real-time, technology-based monitoring systems.